2012
DOI: 10.1523/jneurosci.0204-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Survival Motor Neuron Protein in Motor Neurons Determines Synaptic Integrity in Spinal Muscular Atrophy

Abstract: The inherited motor neuron disease spinal muscular atrophy (SMA) is caused by deficient expression of survival motor neuron (SMN) protein and results in severe muscle weakness. In SMA mice, synaptic dysfunction of both neuromuscular junctions (NMJs) and central sensorimotor synapses precedes motor neuron cell death. To address whether this synaptic dysfunction is due to SMN deficiency in motor neurons, muscle, or both, we generated three lines of conditional SMA mice with tissue-specific increases in SMN expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
208
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(245 citation statements)
references
References 58 publications
24
208
3
1
Order By: Relevance
“…However, the mouse prion promoter used in that study is also active in many nonneuronal cell types and peripheral tissues (Brown et al 1990), which may have contributed to phenotypic rescue. Indeed, several recent studies using various mouse models showed that restoring SMN expression only in motor neurons or pan-neuronally resulted in a limited survival increase (Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012). In accordance with these findings, we recently demonstrated an essential role of SMN expression in peripheral tissues for long-term rescue of severe SMA mice .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, the mouse prion promoter used in that study is also active in many nonneuronal cell types and peripheral tissues (Brown et al 1990), which may have contributed to phenotypic rescue. Indeed, several recent studies using various mouse models showed that restoring SMN expression only in motor neurons or pan-neuronally resulted in a limited survival increase (Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012). In accordance with these findings, we recently demonstrated an essential role of SMN expression in peripheral tissues for long-term rescue of severe SMA mice .…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, in several studies, including our own, selective depletion of SMN in motor neurons induces NMJ defects, and restoration of SMN rescues them, indicating a cell-autonomous mechanism (Park et al 2010;Gogliotti et al 2012;Lee et al 2012;Martinez et al 2012;Sahashi et al 2012Sahashi et al , 2013. This apparent discrepancy may be due to the extremely low SMN levels in motor neurons in these studies.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations